2014
DOI: 10.3109/10717544.2014.909908
|View full text |Cite
|
Sign up to set email alerts
|

pH-responsive thiolated chitosan nanoparticles for oral low-molecular weight heparin delivery: in vitro and in vivo evaluation

Abstract: The aim of present study was to investigate a pH-responsive and mucoadhesive nanoparticle system for oral bioavailability enhancement of low-molecular weight heparin (LMWH). The thioglycolic acid (TGA) was first covalently attached to chitosan (CS) with 396.97 ± 54.54 μmol thiol groups per gram of polymer and then the nanoparticles were prepared with thiolated chitosan (TCS) and pH-sensitive polymer hydroxypropyl methylcellulose phthalate (HPMCP) by ionic cross-linking method. The obtained nanoparticles were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…Among these materials, chitosan has been highly utilized in a number of oral drug delivery systems, including chitosan-based micro- and nanoparticulate drug delivery systems [8994], chitosan-drug conjugates [95, 96], and chitosan macroscale patches [97, 98]. Chitosan is an attractive material for micro/nanofabricated platforms as it is compatible with a number of microfabrication approaches [99, 100], is stable through pH values relevant to GI physiology [101], and has been utilized in microfabricated oral drug delivery systems [58, 102].…”
Section: Strategies To Increase Micro/nanofabricated Oral Drug Delmentioning
confidence: 99%
“…Among these materials, chitosan has been highly utilized in a number of oral drug delivery systems, including chitosan-based micro- and nanoparticulate drug delivery systems [8994], chitosan-drug conjugates [95, 96], and chitosan macroscale patches [97, 98]. Chitosan is an attractive material for micro/nanofabricated platforms as it is compatible with a number of microfabrication approaches [99, 100], is stable through pH values relevant to GI physiology [101], and has been utilized in microfabricated oral drug delivery systems [58, 102].…”
Section: Strategies To Increase Micro/nanofabricated Oral Drug Delmentioning
confidence: 99%
“…This seems to be quite a challenging task, but some attempts are being made in that direction (Martínez-González and Rodríguez 2010). A recent study in rats has shown promising results with the use of nanoparticles prepared with thiolated chitosan and the pH-sensitive polymer hydroxypropyl methylcellulose phthalate (HPMCP) by an ionic cross-linking method (Fan et al 2014). Oral formulations are also being developed for low molecular weight heparin derivatives with anti-angiogenic properties potentially applicable to cancer patients, by chemical conjugation with tetrameric deoxycholic acid and physical complexation with deoxycholylethylamine (Alam et al 2014).…”
Section: Bioengineered Heparin In Mammalian Cellsmentioning
confidence: 99%
“…In another attempt, enoxaparin-loaded NPs possessing both pH-responsive and mucoadhesive properties were formulated using hydroxy propyl methyl cellulose phthalate (HPMCP) as an enteric coating material and thiolated chitosan as mucoadhesive polymer (Fan et al, 2014). A pronounced improvement of oral BAV, which reached 21% was reported holding promise for these systems as potential carriers for oral delivery of LMWHs.…”
Section: Nano-delivery Platforms For Lmwhsmentioning
confidence: 99%
“…Moreover, LMWHs have been used for maintenance of vessel patency during hemodialysis and artery bypass grafting (Patel et al, 2009), prevention of acute bronchoconstrictor responses and airway hyper-responsiveness in asthma (Campo et al, 1999;Ahmed et al, 2000) and regulation of growth factor activity in various vascular disorders and angiogenesis (Reyes-Ortega et al, 2013). Nevertheless, their high anionic charge density, large molecular weight and low stability in acidic stomach pH limit their gastrointestinal absorption, as well as, absorption from other non-invasive routes (Bai et al, 2007;Scala-Bertola et al, 2009;Fan et al, 2014;Hwang & Byun, 2014) rendering the parenteral route the most efficient delivery way so far. However, the need for daily subcutaneous injections (SC) limits its outpatient use (Baldwin et al, 2014).…”
Section: Lmwhs: Chemistry and Pharmacological Actionmentioning
confidence: 99%
See 1 more Smart Citation